Comparisons of angular momentum at takeoff in six types of jumps in women's figure skating - Yamaguchi, Mizuki; Sakurai, Shinji (Frontiers in Sports and Active Living, 2025)
IntroductionIn figure skating, various types of multirotational jumps are becoming increasingly important. Based on mechanical considerations, the angular momentum of the entire body at takeoff can increase the number of rotations in the air. This study aimed to compare and characterize the angular momentum of the entire body and each body part during six different jumps.MethodsSeven female figure skaters performed six double jumps on the ice. The positions of the markers, which were attached to anatomical landmarks, were recorded using a three-dimensional motion analysis system. The angular momenta of the entire body and each body part (trunk, arms, and legs) at takeoff were calculated. The angular momentum was further divided into the transfer term generated by the motion of the body part around the body's center of mass and a local term generated by the rotational motion of the body part itself. A paired t-test was performed to compare all jumps, and multiple comparisons were performed using Holm's method.Results and discussionThe angular momentum of the entire body at takeoff was similar for all jumps. Although the trunk generated a large local term that was similar in all the jumps, the arms and free leg generated large transfer terms with different patterns. This suggests that different strategies may be used to generate angular momentum at takeoff depending on the jump type.